Socioeconomic Inequalities in COVID-19 Incidence During Different Epidemic Phases in South Korea - Yoo, Dae-sung; Hwang, Minji; Chun, Byung Chul; Kim, Su Jin; Son, Mia; Seo, Nam-Kyu; Ki, Myung (Frontiers in Medicine, 2022)
Objective: Area-level socio-economic status (SES) is associated with COVID-19 incidence. However, the underlying mechanism of the association is context-specific, and the choice of measure is still important. We aimed to evaluate socio-economic gradient regarding COVID-19 incidence in Korea based on several area-level SES measures. Methods: Covid-19 incidence and area-level SES measures across 229 Korean municipalities were derived from various administrative regional data. The Bayesian negative binomial model with a spatial autocorrelation term was used to estimate incidence rate ratio (IRR) and relative index of inequality (RII) of each SES factor, with adjustment for covariates. The magnitude of association was compared between two epidemic phases: a low phase (< 100 daily cases, from May 6, 2020, to August 14, 2020) and a rebound phase (> 100 daily cases, from August 15, 2020, to December 31, 2020). Results: Distinctive variability in municipality-specific COVID-19 incidence and SES levels supports area-level analysis, although a relatively low prevalence of COVID-19 in Korea was maintained across the nation. Area-level socio-economic inequalities in COVID-19 incidence between the most disadvantaged region and the least disadvantaged region were observed for non-employment rates (RII = 1.40, 95% credible interval (Crl) = 1.01–1.95) and basic livelihood security recipients (RII = 2.66, 95% Crl = 1.12–5.97) but were not observed for other measures in the low phase. However, the magnitude of the inequalities of these SES variables diminished in the rebound phase. Increase in area-level mobility showed a higher risk of COVID-19 incidence in both the low (IRR = 1.67, 95% Crl = 1.26–2.17) and rebound phases (IRR = 1.28, 95% Crl = 1.14–1.44). When SES and mobility measures were simultaneously adjusted, association of SES with COVID-19 incidence remained significant but only in the low phase, indicating they were mutually independent in the low phase. Conclusion: The level of basic livelihood benefit recipients and non-employment rate showed social stratification of COVID-19 incidence in Korea. Explanation of area-level inequalities in COVID-19 incidence may not be derived only from mobility differences in Korea but, instead, from the country’s own context.